THE ROLE OF THE TEACHER IN THE IMPLEMENTATION OF GUIDANCE AND COUNSELING TO IMPLEMENT DISCIPLINE FOR STUDENTS AT SDN 1 MATANGKULI - Fakhrurrazi; Rahmat Iqbal; Liza Fidiawati (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to describe: 1) Guidance and counseling programs implemented by SDN 1 Matangkuli teachers in instilling discipline; 2) The role of SDN 1 Matangkuli teachers as implementers of guidance and counseling in instilling discipline; 3) Constraints of SDN 1 Matangkuli teachers as implementers of guidance and counseling in instilling discipline; 4) SDN 1 Matangkuli solution as an implementer of guidance and counseling in instilling discipline. This type of research is qualitative research with phenomenological design. Research is conducted by observation, interviews, and documentation and data validity is carried out by triangulation of sources and techniques. The results of this study show: 1) The guidance and counseling program by SDN 1 Matangkuli teachers in instilling discipline is in accordance with the objectives, namely by applying a journal of daily events, spiritual and religiousities; 2) Class teachers actas educators, activity managers, consultants, role models/examples, problem solver; 3) The obstacles faced by SDN 1 Matangkuli teachers are the competence of class teachers as supervisors who are not qualified, less experienced and professional, guidance and counseling management that has not been organized and lack of communication with professional experts and guardians; 4) The solutions obtained by SDN 1 Matangkuli teachers are increasing the ability of class teachers as guides improving guidance and counseling management, conducting socialization by involving experts and communicating with parents in seeing the development of students.